Qazaqliq, or, Ambitious brigandage, and the formation of the Qazaqs : state and identity in post-Mongol central Eurasia - Lee, Joo-Yup. (Studies in Persian Cultural History, 2016)
In Qazaqlïq , or Ambitious Brigandage , and the Formation of the Qazaqs Joo-Yup Lee examines the formation of new group identities, with a focus on the Qazaqs, in post-Mongol Central Eurasia within the context of qazaqlïq , or the qazaq way of life, a custom of political vagabondage widespread among the Turko-Mongolian peoples of Central Asia and the Qipchaq Steppe during the post-Mongol period. Utilizing a broad range of original sources, the book suggests that the Qazaqs, as well as the Shibanid Uzbeks and Ukrainian Cossacks, came into existence as a result of the qazaq , or "ambitious brigand," activities of their founders, providing a new paradigm for understanding state formation and identity in post-Mongol Central Eurasia.